Impact of chronic kidney disease on long‐term clinical outcomes of everolimus‐eluting stent implantation: A subanalysis of the Tokyo‐MD PCI registry. Issue 1 (4th February 2019) - Miyazaki, Toru; Ashikaga, Takashi; Asano, Mitsutoshi; Sasaoka, Taro; Kurihara, Ken; Yoshikawa, Shunji; Isobe, Mitsuaki; ,
Abstract: Objective: The aim of the study was to investigate the impact of chronic kidney disease (CKD) on the 5‐year clinical outcomes of everolimus‐eluting stent (EES) implantation. Background: Recent studies have demonstrated the safety and efficacy of EES. However, limited information exists on the long‐term clinical outcomes associated with CKD. Methods: The Tokyo‐MD PCI study is a multi‐center observational study designed to describe the clinical outcomes of unselected patients after EES implantation. In this subanalysis, patients on maintenance hemodialysis were excluded, and patients with (n = 316) or without (n = 1, 424) CKD were evaluated for their 5‐year incidence rates of major adverse cardiac events (MACEs), defined as death, non‐fatal myocardial infarction, ischemia driven target lesion revascularization (ID‐TLR), and stent thrombosis (ST). Results: The mean and median follow‐up duration were 1, 391 ± 557 days and 1, 769 days (interquartile range, 1, 012–1, 800 days), respectively. Although the incidence of ID‐TLR and ST was similar between patients with and without CKD (4.9% vs. 3.7%, P  = 0.26, 0.5% vs. 1.0%, P  = 0.20, respectively), cardiac death and MACE were significantly higher in patients with CKD than in those without CKD (6.5% vs. 2.9%, P  = 0.007, 26.9% vs. 14.0%, P  < 0.001, respectively). In multivariate analysis, CKD was an independent predictor of MACE (hazard ratio 1.22 [95% confidence interval 1.04–1.43], P = 0.01). Conclusions: Patients with CKD had similar ID‐TLR and ST rates as those without CKD at 5 years after EES implantation. The risk of long‐term MACEs appeared to be associated with CKD.